The double CUE domain of chromatin remodelling factor SMARCAD1 - West, P; Philip West (2012)
ATP-dependent chromatin remodellers represent a class of proteins that restructure chromatin through the action of a conserved helicase-like ATPase domain. Remodellers typically have several accessory binding domains alongside the ATPase. These confer target specificity and most commonly recognise histone post-translational modifications. SMARCAD1 is a ubiquitous chromatin remodeller involved with DNA replication and re- pair. It binds directly to PCNA at the site of DNA replication and recruits co-repressor KAP1 in order to silence newly produced chromatin. In contrast to most other chromatin remodellers, SMARCAD1 does not contain several different types of accessory domains. Only two CUE do- mains have been identified in addition to the SMARCAD1 core ATPase domain. CUE domains are a type of helical ubiquitin-binding domain. This thesis presents the findings of an investigation into the structure and function of the SMARCAD1 double CUE domain. The solution NMR structure is presented with results from NMR binding experiments mapped onto the structure. Each CUE domain was found to be an independent helix bundle connected by a dynamic flexible linker. The N-terminal CUE domain, CUE-1, binds ubiquitin and has an adjacent SUMO (a ubiquitin-like protein) binding motif on a protruding extended helix. The C-terminal CUE domain, CUE-2, has a very similar structure to several published CUE domains but does not bind ubiquitin due to a charged substitution at a highly conserved CUE consensus position. The SMARCAD1 double CUE domain binds KAP1 from nuclear extract and is likely to mediate the interaction between SMARCAD1 and KAP1. SMARCAD1 double CUE domain is not involved with PCNA binding.